Kepastian Hukum Atas Status Tanah Adat Setelah Berlakunya Undang-Undang Pokok Agraria - Zahra, Mutia; Priyono, Ery Agus (Legal Standing : Jurnal Ilmu Hukum, 2025)
On September 24, 2024, the Basic Agrarian Law (UUPA) was enacted and implemented, which is the main legal basis for land regulation in Indonesia. Before the UUPA was enacted, land regulations in Indonesia were still based on unwritten customary law and Western civil law inherited from the colonial era. In practice, many Indonesian people control land based on customary law, which often does not have valid written evidence to show ownership rights. Therefore, regulations regarding land rights are still often complicated and prone to disputes. The UUPA is present as an implementation of Article 33 paragraph (3) of the 1945 Constitution which mandates that the earth, water, and natural resources must be controlled by the state and used as much as possible for the prosperity of the people. The main objective of the UUPA is to create a just and prosperous society, as well as to provide legal certainty regarding land ownership and provide protection to people who have ownership rights to customary land, the UUPA allows the conversion of ownership rights to customary land into ownership rights in accordance with the provisions of the UUPA. The process of proving land rights in the UUPA can be done in several ways, such as land registration followed by the issuance of a land certificate, the issuance of a Land Rights Certificate (SKHAT) by the Village Head or Lurah which is authorized by the Sub-district Head, and also with physical control of the land which is proven by the existence of plants or buildings on the land. Through the UUPA, the government plays a role in equalizing land distribution and improving natural resource management, as part of agrarian reform. This is important to create a fairer and more equitable land ownership system throughout Indonesia.